STRATEGI BARU DALAM PENGEMBANGAN SDM UNTUK PENGURUS PEMERINTAHAN DESA: MENINGKATKAN KUALITAS PELAYANAN DAN EFEKTIVITAS KEPEMIMPINAN - Syaifuddin (Jurnal Kreatif : Karya Pengabdian untuk Masyarakat Aktif dan Inovatif, 2024)
This service activity aims to improve the quality of service and effectiveness of leadership at the village level by strengthening the human resource capacity of village government administrators. By involving various parties, such as local governments, educational institutions and civil society organizations, a series of structured and sustainable education, training and mentoring programs were carried out. The results of this activity show a significant increase in the knowledge, skills and attitudes of village administrators regarding public service management and leadership. Implementation of new practices, increased community participation, application of information technology, and changes in organizational culture are positive indications of the success of this strategy. However, further efforts are still needed in routine monitoring and evaluation, increasing collaboration between institutions, and encouraging community participation to ensure the continuity and success of these human resource development efforts in the long term. It is hoped that the results of this activity can make a significant contribution in improving the quality of life and public services in Cipagalo Village and in other similar places.